2001
DOI: 10.2475/ajs.301.8.683
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of fossilization of the soft-bodied and lightly armored faunas of the Burgess Shale and of some other classical localities

Abstract: The splendid preservation of the Middle Cambrian Burgess Shale fauna, a fauna of exceptional importance for our understanding of the evolution of life, has not been adequately explained. Preservation of diagenetically altered remnants of the original organic tissues and formation of chlorite/illite coatings and cuticle replacements, both documented in the Burgess Shale fossils though not necessarily occurring together, can be understood as products of the same mechanism of fossilization of soft tissues. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 201 publications
(176 reference statements)
3
86
0
Order By: Relevance
“…The first explanation attributes the abundance of exceptionally preserved fossil assemblages in the upper Neoproterozoic-lower Paleozoic to seawater chemistry, which given its unique make-up in that interval, supported a multitude of preservational processes and opened all taphonomic windows. High silica allowed for silicification (Knoll, 1985;Maliva et al, 1989); influx of phosphate promoted phosphatization ; and aspects that inhibited degradative chemistry resulted in organic preservation (Butterfield, 1990;Gaines et al, 2012aGaines et al, , 2012bOrr et al, 1998;Petrovich, 2001). Yet, as our conceptual model shows, the major taphonomic processes do not occur under entirely unique environmental conditions.…”
Section: Exceptional Preservation Through Time In Marine Settingsmentioning
confidence: 99%
“…The first explanation attributes the abundance of exceptionally preserved fossil assemblages in the upper Neoproterozoic-lower Paleozoic to seawater chemistry, which given its unique make-up in that interval, supported a multitude of preservational processes and opened all taphonomic windows. High silica allowed for silicification (Knoll, 1985;Maliva et al, 1989); influx of phosphate promoted phosphatization ; and aspects that inhibited degradative chemistry resulted in organic preservation (Butterfield, 1990;Gaines et al, 2012aGaines et al, , 2012bOrr et al, 1998;Petrovich, 2001). Yet, as our conceptual model shows, the major taphonomic processes do not occur under entirely unique environmental conditions.…”
Section: Exceptional Preservation Through Time In Marine Settingsmentioning
confidence: 99%
“…Despite reports of accelerated carcass decay associated with some sediments (e.g., Plotnick 1986;Allison 1988;Briggs and Kear 1993), most models for BST preservation invoke mineralspecific diagenesis as an essential factor, either by suppressing normal enzyme-microbial-based decay processes (e.g., Butterfield 1990Butterfield , 1995Gaines et al 2005Gaines et al , 2012 or secondarily by enhancing the recalcitrance of relatively labile substrates (e.g., Orr et al 1998;Petrovich 2001). Surprisingly, there has been little attempt to test these various models, though Martin et al (2004) have shown that sedimentary particles will adhere to lobster eggs in the presence of bacteria, and Naimark et al (2013) have documented substantially enhanced preservation of Artemia when they are buried in kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…By and large, kerogenization has been attributed to many of the same facilitating conditions, mostly related to rapid burial into anoxic/dysoxic palaeoenvironments 15 . While numerous other palaeoenvironmental and diagenetic considerations have been invoked for kerogenization, such as interactions with clays 6,16 or ferrous iron 17 , high alkalinity 15,18 and oxidant restriction (that is, lack of sulfate for BSR) through early diagenetic sealing 18 (though see also ref. 19), the common association of kerogenized fossils with pyrite 1,6,12,16,[20][21][22][23][24] bolsters the interrelationship of these taphonomic processes.…”
mentioning
confidence: 99%